Will mark as brainliest if correct
![Will mark as brainliest if correct class=](https://us-static.z-dn.net/files/d84/beb81f72bee8d40d0c6a731db51a9ec3.png)
Answer:
x=((log(81))/(log(3))+2)/3
Step-by-step explanation:
so what you want to do is get 3x-2 out of the exponent
you can do that by using log
so apply log to both sides and you get
log(81)=(3x-2)log(3)
the 3x-2 is moved in front of the log due to a log rule
then (log(81))/(log(3))=3x-2
(log(81))/(log(3))+2=3x
((log(81))/(log(3))+2)/3=x
then use a calculator to find the exact value
hope this helps im sorry my explanation is a bit confusing, ask any questions you have